Educating patients about warfarin therapy using information technology: A survey on healthcare professionals’ perspectives - Nasser, Sayeed (Centro de Investigaciones y Publicaciones Farmaceuticas, 2012)
OBJECTIVE: To explore healthcare professionals' views about the benefits and challenges of using information technology (IT) resources for educating patients about their warfarin therapy. METHODS: A cross-sectional survey of both community and hospital-based healthcare professionals (e.g., doctors, pharmacists and nurses) involved using a purpose-designed questionnaire. The questionnaires were distributed using a multi-modal approach to maximise response rates. RESULTS: Of the total 300 questionnaires distributed, 109 completed surveys were received (43.3% response rate). Over half (53.2%) of the healthcare participants were aged between 40-59 years, the majority (59.5%) of whom were female. Fifty nine (54.1%) participants reported having had no access to warfarin-specific IT-based patient education resources, and a further 19 (38.0%) of the participants who had IT-access reported that they never used such resources. According to the healthcare participants, the main challenges associated with educating their patients about warfarin therapy included: patient-related factors, such as older age, language barriers, cognitive impairments and/or ethnic backgrounds or healthcare professional factors, such as time constraints. The healthcare professionals reported that there were several aspects about warfarin therapy which they found difficult to educate their patients about which is why they identified computers and interactive touch screen kiosks as preferred IT devices to deliver warfarin education resources in general practices, hospital-based clinics and community pharmacies. At the same time, the healthcare professionals also identified a number of facilitators (e.g., to reinforce warfarin education, to offer reliable and easily comprehensible information) and barriers (e.g., time and costs of using IT resources, difficulty in operating the resources) that could impact on the effective implementation of these devices in educating patients about their warfarin therapy. CONCLUSIONS: The findings of the study suggest that there is a need for improving healthcare professionals' use of, and access to IT-based warfarin education resources for patients. The study findings also suggest addressing the concerns raised by the healthcare professionals when implementing such IT resources successfully to help educate patients about their warfarin therapy.